Birth attendants as perinatal verbal autopsy respondents in low-and middle-income countries: a viable alternative? - C Engmann; A Garces; I Jehan; J Ditekemena; M Phiri; V Thorsten; M Mazariegos; E Chomba; O Pasha; A Tshefu; D Wallace; EM McClure; et al.
OBJECTIVE: To assess the feasibility of using birth attendants instead of bereaved mothers as perinatal verbal autopsy respondents. METHODS: Verbal autopsy interviews for early neonatal deaths and stillbirths were conducted separately among mothers (reference standard) and birth attendants in 38 communities in four developing countries. Concordance between maternal and attendant responses was calculated for all questions, for categories of questions and for individual questions. The sensitivity and specificity of individual questions with the birth attendant as respondent were assessed. FINDINGS: For early neonatal deaths, concordance across all questions was 94%. Concordance was at least 95% for more than half the questions on maternal medical history, birth attendance and neonate characteristics. Concordance on any given question was never less than 80%. Sensitivity and specificity varied across individual questions, more than 80% of which had a sensitivity of at least 80% and a specificity of at least 90%. For stillbirths, concordance across all questions was 93%. Concordance was 95% or greater more than half the time for questions on birth attendance, site of delivery and stillborn characteristics. Sensitivity and specificity varied across individual questions. Over 60% of the questions had a sensitivity of at least 80% and over 80% of them had a specificity of at least 90%. Overall, the causes of death established through verbal autopsy were similar, regardless of respondent. CONCLUSION: Birth attendants can substitute for bereaved mothers as verbal autopsy respondents. The questions in existing harmonized verbal autopsy questionnaires need further refinement, as their sensitivity and specificity differ widely.